Implementation of Enterprise Architecture Zachman Framework at Jewelry Company - Annisa Paramaswary Aslam; Hannan Fadlurahman; Arnes Yuli Vandika; Muh Arnesta Arnanda; Muh Reza Abdillah (Indonesian Journal of Enterprise Architecture, 2024)
Jewelry Company is a company that produces jewelry by providing the best quality to its consumers. In its development, the jewelry company has a factory that produces various types of jewelry including gold, silver, ruby, gems, topaz and sapphire. However, IS/IT planning within the company is still not maximizing the use of IS/IT that should be implemented within a company. Therefore, this company needs a more strategic planning to support business goals that are in line with business strategy and IS/IT strategy. Enterprise Architecture Planning was chosen as a guide and the Zachman Framework as a design method which consists of six lines, namely scope, enterprise model, system model, technology constrained model, retailed representations, and functioning enterprise, as well as six columns consisting of what, how, where, who, when, and why. The results of this research are a proposed architectural design that is recommended to companies, which is expected to fully support ongoing business activities so that they are more optimal and effective.